UAVs Intercepting Possibility Substantiation: Economic and Technical Aspects - Pohasii, Serhii; Korolov, Roman; Vorobiov, Bohdan; Bril, Mykhailo; Serhiienko, Olena; Milevskyi, Stanislav (My University, 2022)
The main problem in the military and commercial sector is to detect the UAV and carry out a successful attack to neutralize it. In this case, sets of various tools from electronic warfare to missile systems can be used for destruction. Small, lightweight UAVs can be shot down with small arms, man-portable EW jamming, or rocket/cannon weapons, requiring more ammunition, limited energy, or high projectile costs. The most pressing issue is the definition of a tool that has intelligent computer control systems, sufficient technical characteristics, is mobile, easy to operate and economically feasible for use in the destruction of low-cost UAVs with a high coefficient of harm. This article discusses the economic and technical feasibility of using a UAV-controlled interceptor using the parallel approach guidance method.
Keywords: UAV interceptor; countermeasures against UAV; UAV guidance methods; economic and technical efficiency; parallel approach method